Dysregulated Interferon Response and Immune Hyperactivation in Severe COVID-19: Targeting STATs as a Novel Therapeutic Strategy - Eskandarian Boroujeni, Mahdi; Sekrecka, Agata; Antonczyk, Aleksandra; Hassani, Sanaz; Sekrecki, Michal; Nowicka, Hanna; Lopacinska, Natalia; Olya, Arta; Kluzek, Katarzyna; Wesoly, Joanna; Bluyssen, Hans A. R. (Frontiers in Immunology, 2022)
A disease outbreak in December 2019, caused by a novel coronavirus SARS-CoV-2, was named COVID-19. SARS-CoV-2 infects cells from the upper and lower respiratory tract system and is transmitted by inhalation or contact with infected droplets. Common clinical symptoms include fatigue, fever, and cough, but also shortness of breath and lung abnormalities. Still, some 5% of SARS-CoV-2 infections progress to severe pneumonia and acute respiratory distress syndrome (ARDS), with pulmonary edema, acute kidney injury, and/or multiple organ failure as important consequences, which can lead to death. The innate immune system recognizes viral RNAs and triggers the expression of interferons (IFN) IFNs activate anti-viral effectors and components of the adaptive immune system by activating members of the STAT and IRF families that induce the expression of IFN-stimulated genes (ISG)s. Among other coronaviruses, such as Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV, common strategies have been identified to antagonize IFN signaling. This typically coincides with hyperactive inflammatory host responses known as the “cytokine storm” that mediate severe lung damage. Likewise, SARS-CoV-2 infection combines a dysregulated IFN response with excessive production of inflammatory cytokines in the lungs. This excessive inflammatory response in the lungs is associated with the local recruitment of immune cells that create a pathogenic inflammatory loop. Together, it causes severe lung pathology, including ARDS, as well as damage to other vulnerable organs, like the heart, spleen, lymph nodes, and kidney, as well as the brain. This can rapidly progress to multiple organ exhaustion and correlates with a poor prognosis in COVID-19 patients. In this review, we focus on the crucial role of different types of IFN that underlies the progression of SARS-CoV-2 infection and leads to immune cell hyper-activation in the lungs, exuberant systemic inflammation, and multiple organ damage. Consequently, to protect from systemic inflammation, it will be critical to interfere with signaling cascades activated by IFNs and other inflammatory cytokines. Targeting members of the STAT family could therefore be proposed as a novel therapeutic strategy in patients with severe COVID-19.